Arylation of benzyl amines with aromatic nitriles. Issue 84 (4th October 2018) - Lei, Yingjie; Yang, Ju; Qi, Rupeng; Wang, Shan; Wang, Rui; Xu, Zhaoqing
Abstract : The C(sp 3 )–H arylation of benzyl amines with aromatic nitriles for the synthesis of diarylmethylamines was realized without the assistance of transition-metal and photoirradiation. Abstract : In the past years, the activations of aromatic nitriles for radical arylations under photoirradiation have been developed. We here report the first example of radical arylations using aromatic nitriles without the assistance of photoirradiation. Importantly, with this method, the direct arylation of C(sp 3 )–H in benzyl amines provided a practical method for the synthesis of diarylmethylamines without the use of precious transition metal catalysts.